Does ginger supplementation lower blood pressure? A systematic review and meta‐analysis of clinical trials. (11th April 2019) - Hasani, Hossein; Arab, Arman; Hadi, Amir; Pourmasoumi, Makan; Ghavami, Abed; Miraghajani, Maryam
Abstract : The aim of the present systematic review and meta‐analysis was to determine the efficacy of ginger supplementation on blood pressure (BP). PubMed, Scopus, ISI Web of Science, Cochrane Library, and Google Scholar were comprehensively searched until September 2018. Human clinical trials, which reported the effect of ginger supplementation on aortic and/or brachial BP, were included. Mean differences were pooled using a random effects model. Standard methods were used for assessment of heterogeneity, sensitivity analysis, and publication bias. Total of six randomized clinical trials (345 participants) were included in the meta‐analysis. Pooled analysis suggested that ginger supplementation can reduced systolic BP (MD: −6.36 mmHg, 95% confidence interval [−11.27, −1.46]; I 2  = 89.8%; P  = .011) and diastolic BP (MD: −2.12 mmHg, 95% confidence interval [−3.92, −0.31]; I 2  = 73.4%; P  = .002). When studies were categorized based on participants' mean age, ginger dosage and duration of intervention, systolic BP and diastolic BP were significantly decreased only in the subset of studies with mean age ≤ 50 years, follow‐up duration of ≤8 weeks and ginger doses ≥3 g/d. Our findings revealed that ginger supplementation has favorable effects on BP. Nonetheless, further studies are warranted before definitive conclusions may be reached.